2004
DOI: 10.1016/s1090-3801(03)00082-x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pain thresholds of tender point sites in patients with fibromyalgia and in healthy controls

Abstract: Pressure pain threshold (PPT) is defined as the minimum force applied which induces pain. This measure has proven to be commonly useful in evaluating tenderness symptom. Our aim was to study the intra-examiner reproducibility of PPT measurement, define cutoffs in normal groups, and compare these results with patients with fibromyalgia (FM). Fifty healthy females, 50 healthy males, and 20 patients with FM participated in the study. PPTs were assessed for 18 specific tender point sites by a dolorimeter. The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(83 citation statements)
references
References 32 publications
9
67
1
6
Order By: Relevance
“…Pain questionnaires used to assess subjective neck pain include the Neck Disability Index (NDI) 12,13) and Neck Pain and Disability Scale (NPDS) 14) . Pressure algometers are used widely in research and clinical medicine to measure the pressure-pain threshold (PPT) objectively [15][16][17] . The…”
Section: Introductionmentioning
confidence: 99%
“…Pain questionnaires used to assess subjective neck pain include the Neck Disability Index (NDI) 12,13) and Neck Pain and Disability Scale (NPDS) 14) . Pressure algometers are used widely in research and clinical medicine to measure the pressure-pain threshold (PPT) objectively [15][16][17] . The…”
Section: Introductionmentioning
confidence: 99%
“…Patients with fibromyalgia (FM) have muscle weakness (1), widespread muscle pain, and lower pressure pain thresholds of tender sites in the upper and lower limbs (2,3). In addition to pain, the most prominent symptoms in FM are localized to peripheral soft tissues, and there have been numerous studies of abnormalities in muscle structure and function in individuals with FM.…”
Section: Introductionmentioning
confidence: 99%
“…The crosssectional area of the quadriceps femoris muscle has been reported to be within normal ranges in persons with FM (5,6). However, some studies have shown that maximal isometric and dynamic muscle strength in short tests (1)(2)(3)(4)(5) repetitions) is lower in persons with FM than in healthy individuals (1,5,7,8); however, these reports have been contradicted in the longer tests that are more related to resistance (9,10). The reduced maximal muscle strength of knee extensors has been associated with lower outcomes in functional tests related to daily living (sit up and sit down on a chair, walking) in persons with FM (11) and with the increase of disability, especially in females with rheumatoid arthritis (12).…”
Section: Introductionmentioning
confidence: 99%
“…
IntroductionPrevious reports have demonstrated high intra-and interrater reliability for assessment of pressure pain thresholds (PPT) in clinical [1][2][3][4] and healthy subjects [5][6][7][8][9][10][11]. However, many of the earlier reliability analyses used Pearson's r correlation coefficient [e.g.
…”
mentioning
confidence: 99%